Bioinformatic Prediction and Characterization of Proteins in Porphyra dentata by Shotgun Proteomics - Yang, Mingchang; Ma, Lizhen; Yang, Xianqing; Li, Laihao; Chen, Shengjun; Qi, Bo; Wang, Yueqi; Li, Chunsheng; Yang, Shaoling; Zhao, Yongqiang (Frontiers in Nutrition, 2022)
Porphyra dentata is an edible red seaweed with high nutritional value. It is widely cultivated and consumed in east Asia and has vast economic benefits. Studies have found that P. dentata is rich in bioactive substances and is a potential natural resource. In this study, label-free shotgun proteomics was applied to identify and characterize complete harvest proteins in P. dentata. A total of 13,046 different peptides were identified and 419 target proteins were characterized. Bioinformatics was used to study protein characteristics, functional expression, and interaction of two important functional annotations, amino acid and carbohydrate metabolism. Potential bioactive peptides, protein structure, and potential ligand conformations were predicted and the results suggest that bioactive peptides may be utilized as high-quality active fermentation substances and potential targets for drug production. Our research integrated of the global protein database, the first time bioinformatic analysis of the P. dentata proteome during the harvest period, improves the information database construction, and provides a framework for future research on the basis of a comprehensive understanding.